Rapid self-heating and internal temperature sensing of lithium-ion batteries at low temperatures. (10th November 2016) - Zhang, Guangsheng; Ge, Shanhai; Xu, Terrence; Yang, Xiao-Guang; Tian, Hua; Wang, Chao-Yang
Graphical abstract: Highlights: Self-heating lithium-ion battery (SHLB) structure provided a practical solution to the poor performance at subzero temperatures. We report an improved SHLB that heats from −20 °C to 0 °C in 12.5 seconds, or 56% more rapidly, while consuming 24% less energy than previously reported. The nickel foil heating element embedded inside a SHLB cell plays a dominant role in rapid self-heating. The embedded nickel foil can simultaneously perform as an internal temperature sensor (ITS). 2-sheet design self-heats faster than 1-sheet design due to more uniform internal temperature distribution. Abstract: The recently discovered self-heating lithium-ion battery structure provided a practical solution to the poor performance at subzero temperatures that has hampered battery technology for decades. Here we report an improved self-heating lithium-ion battery (SHLB) that heats from −20 °C to 0 °C in 12.5 seconds, or 56% more rapidly, while consuming 24% less energy than that reported previously. We reveal that a nickel foil heating element embedded inside a SHLB cell plays a dominant role in self-heating and we experimentally demonstrate that a 2-sheet design can achieve dramatically accelerated self-heating due to more uniform internal temperature distribution. We also report, for the first time, that this embedded nickel foil can simultaneously perform as an internal temperature sensor (ITS) due to the perfectly linear relationship between the foil's electrical resistance and temperature.